Internalization of Ineffective Platinum Complex in Nanocapsules Renders It Cytotoxic - Vrana, Oldrich; Novohradsky, Vojtech; Medrikova, Zdenka; Burdikova, Jana; Stuchlikova, Olga; Kasparkova, Jana; Brabec, Viktor (Chemistry (Weinheim an der Bergstrasse, Germany), 2016)
Anticancer therapy by platinum complexes, based on nanocarrier-based delivery, may offer a new approach to improve the efficacy and tolerability of the platinum family of anticancer drugs. The original rules for the design of new anticancer platinum drugs were affected by the fact that, although cisplatin (cis-[PtCl2 (NH3)2) was an anticancer drug, its isomer transplatin was not cytotoxic. For the first time, it is demonstrated that simple encapsulation of an inactive platinum compound in phospholipid bilayers transforms it into an efficient cytotoxic agent. Notably, the encapsulation of transplatin makes it possible to overcome the resistance mechanisms operating in cancer cells treated with cisplatin and prevents inactivation of transplatin in the extracellular environment. It is also shown that transplatin delivered to the cells in nanocapsules, in contrast to free (nonencapsulated) complex, forms cytotoxic cross-links on DNA.
Keywords: cancer; Platinum; platina; platinum; cisplatina; Cisplatin; Platinum Compounds; Liposomes; Nanocapsules; DNA; lidé; fosfolipidy; adukty DNA; Antineoplastic Agents; protinádorové látky; sloučeniny platiny; liposomy; DNA Adducts; Phospholipids; nanokapsle; liposomes; phospholipids; Humans